2004
DOI: 10.1038/sj.bjc.6601955
|View full text |Cite
|
Sign up to set email alerts
|

Establishing long-term survival and cure in young patients with Ewing's sarcoma

Abstract: This paper investigates the potential for long-term survivorship for young patients diagnosed with Ewing's sarcoma. Data are examined from two successive UKCCSG Ewing's Tumour studies (ET-1 and ET-2). Patients have been followed for up to 20 years. These studies had suggested that better 5-year survival with ET-2 over the earlier ET-1 was achieved by replacing cyclophosphamide by ifosfamide and increasing the dose of doxorubicin in a four-drug chemotherapy regimen. The updated hazard ratio, stratified for meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Mixture survival models have been applied to colon cancer data collected in Finland 1953–1992 6 and Weston et al . have described the long‐term survival following diagnoses of Ewing's sarcoma, quantifying the cure in young patients 37…”
Section: Discussionmentioning
confidence: 99%
“…Mixture survival models have been applied to colon cancer data collected in Finland 1953–1992 6 and Weston et al . have described the long‐term survival following diagnoses of Ewing's sarcoma, quantifying the cure in young patients 37…”
Section: Discussionmentioning
confidence: 99%
“…Second, the five year survival rate of disease increased in the past three decades from 42% to 58% and then to more than 60% worldwide (Oberlin et al, 2001;Haeusler et al, 2010). Increasing survival continued until some specialists suggested that 'cure' is possible for patients with Ewing's sarcoma (Weston et al, 2004). Third the five year survival rates in recurrent disease is only 13% (Leavey et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The application of the Weibull distribution function approaches multiple clinical applications and it is well established theoretically and practically [9][10][11][12]. It has been used for a long time for survival description in gerontology [13,14] and in oncology [15] as well.…”
Section: Methodsmentioning
confidence: 99%